Sex differences in aneurysm morphologies and clinical outcomes in ruptured anterior communicating artery aneurysms: a retrospective study. Issue 4 (15th April 2016) - Lin, Boli; Chen, Weijian; Ruan, Lei; Chen, Yongchun; Zhong, Ming; Zhuge, Qichuan; Fan, Liang Hao; Zhao, Bing; Yang, Yunjun
Abstract : Objectives: Ruptured anterior communicating artery (ACoA) aneurysms occur more frequently in men. The purpose of the study was to investigate sex difference in aneurysm morphologies and clinical outcomes in patients with ruptured ACoA aneurysms. Setting: A tertiary referral hospital. Participants: A total of 574 consecutive patients with ACoA aneurysms were admitted to our hospital from December 2007 to February 2015. In all, 474 patients (257 men and 217 women) with ruptured ACoA aneurysms were included in the study. Main outcome measures: Aneurysm morphologies were measured using computed tomographic angiography and clinical outcomes were measured with Glasgow coma score at discharge. Results: The aneurysm sizes (p=0.001), aneurysm heights (p=0.011), size ratios (p<0.001), flow angles (p=0.047) and vessel angles (p=0.046) were larger in the male patients than in the females. The female patients more often had larger vessel sizes (p=0.002). Multivariate logistic analysis revealed that significant differences in aneurysm morphologies between men and women were aneurysm size (OR 1.1, 95% CI 1.0 to 1.3; p=0.036), aneurysm height (OR 0.8, 95% CI 0. to 0.9; p=0.006) and size ratio (OR 1.4, 95% CI 0.5 to 1.7; p=0.001). There were no statistically significant differences in the outcomes between men and women (OR 1.0, 95% CI 0.6 to 1.7, p=0.857). Conclusions: The men were independently associated with larger aneurysm sizes, greater aneurysm heights and larger size ratios. Sex was not a risk factor for poor outcome in patients with ruptured ACoA aneurysms.